2011
DOI: 10.5888/pcd9.100271
|View full text |Cite
|
Sign up to set email alerts
|

Using a Socioeconomic Position Index to Assess Disparities in Cancer Incidence and Mortality, Puerto Rico, 1995-2004

Abstract: Introduction Evaluation of the extent of socioeconomic inequalities in cancer incidence and mortality is essential to generate hypotheses in population health research and provides evidence for population-based strategies for comprehensive cancer control. The objective of this study was to create an area-based socioeconomic position (SEP) index to assess possible socioeconomic disparities in incidence and mortality of selected cancers in Puerto Rico. Methods Data for cancer incidence and mortality from 1995 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 14 publications
9
37
1
Order By: Relevance
“…However, this registry provides the largest nationwide data from a population-based cancer registry, and the results we report still provide evidence of the impact of enhanced detection on the increase in thyroid cancer incidence and lead to further investigation and discussion. Our findings are in agreement with other studies that have suggested that higher SES is associated with higher thyroid cancer incidence (18)(19)(20). Morris et al reported a lower incidence of thyroid cancer diagnosis among individuals residing in poorer versus wealthier zip code areas (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, this registry provides the largest nationwide data from a population-based cancer registry, and the results we report still provide evidence of the impact of enhanced detection on the increase in thyroid cancer incidence and lead to further investigation and discussion. Our findings are in agreement with other studies that have suggested that higher SES is associated with higher thyroid cancer incidence (18)(19)(20). Morris et al reported a lower incidence of thyroid cancer diagnosis among individuals residing in poorer versus wealthier zip code areas (18).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, if the observed increase in thyroid cancer is due to enhanced detection, patients with higher SES, who generally have better access to health care-including diagnostic tests-would be expected to have a greater increase in thyroid cancer incidence than patients with lower SES. Several studies have indicated that higher SES is indeed associated with higher thyroid cancer incidence (18)(19)(20), but there is limited understanding of changing trends in thyroid cancer incidence over time by SES or how tumor size might factor into these associations. In an effort to elucidate the contribution of enhanced detection to the recent increases in thyroid cancer incidence, we compared thyroid cancer incidence trends between low-and high-SES counties in the United States over the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in tumor location between socioeconomic groups (gastric cancer is more common in lower classes, whereas colorectal cancer is more common in upper classes) has been noted in previous studies conducted in Latin American populations (31). Although average patient age was rather low in both groups evaluated in the present study, previous studies in Latin America have reported similar results, especially for gastric cancer (32).…”
Section: Discussionsupporting
confidence: 80%
“…Also, it may be proposed that prostate-specific antigen testing (PSA) is responsible for an increase in low-grade prostate cancer in advantaged men, but it does not explain the overall increases in all grades as 37% lower inci- dence was revealed among the most disadvantaged compared to the most advantaged (35). Although higher levels of SES were significantly associated with an increased risk of prostate cancer (36,37), no evidence was found on the racially uniform population of Caucasians who received free health care (38).…”
Section: Discussionmentioning
confidence: 99%